Generational Divide in Digital Banking: Comparing Experience and Expectation across Generations X, Y, and Z - Thasleena, K. Fathimath; Santhi, P. (Indian Journal of Information Sources and Services, 2025)
Digital banking has become a crucial component of today’s financial environment with its ease of use and accessibility. How Generation X, Generation Y, and Generation Z have embraced and changed digital banking is distinct. The demands, tastes, and experiences of these generational groups with digital banking services differ. This study aims to examine digital banking experience and expectations of customers among generations X, Y, and Z in the Malabar region of Kerala, which has a rich and diverse cultural heritage. A comprehensive interview was conducted with digital banking customers, representing a comparable proportion of each generation. The result of the Tukey HSD Post Hoc test indicates that the experience and expectations of Generation X, Y, and Z differ about digital banking. Digital banking is seen as complex by Generation X, but it is preferred for quick transactions by Generation Y, and more personalised care is desired by Generation Z. This study provides banks with a thorough strategic foundation for adapting to changing customer expectations across generations.